Does the Home Market Effect Arise in a Three-Country Model? - Jens Südekum (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2005)
It is uncertain whether the fundamental 'home market effect' (HME) generalizes from a two-country model to a more realistic setting with multiple countries. We present a three-country version of the seminal model by Krugman (1980) and analyse under which circumstances the HME is present once third country effects are taken into account. We show that both expenditure shifts and exogenous enlargements among foreign countries can rule out the HME.
Keywords: R12; F14; F12; 330; New trade theory; home market effect; hub effect; Neue Aussenhandelstheorie; Export; Marktanteil; Mehr-Länder-Modell; Theorie